Nutraceuticals in the management of type 2 diabetes - De Gennaro Colonna, Vito (La Medicina del Lavoro, 2020)
Background: The prevalence of type 2 diabetes mellitus (T2DM) is dramatically increasing worldwide. Hypergly-cemia and dyslipidemia, the two major components of this metabolic disorder, lead to accelerated ath-erosclerosis, coronary heart disease, chronic kidney disease and increase in the mortality rate. In recent years a growing number of hypoglycemic drugs have become available. However, in a remarkable number of patients the disease control is not fully satisfactory. Thus the search of new antidiabetic agents with minimal side effects is mandatory. In this context, nutraceuticals (bioactive compounds mostly of plant origin) can play a positive role in the management of T2DM, also in association with hypoglycemic drugs. An interesting feature of some nutraceuticals is their ability to improve not only the glycemic control but also the lipidic profile (berberine), the antioxidant status (silymarin) or endo-thelium dependent -vasodilator function (Pycnogenol) of the patients.